Ideologi pada Novel Rapijali: 1 Mencari Karya Dee Lestari: Analisis Wacana Kritis - Ul Haq, Zia; Usman, Usman; Haliq, Abdul (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
The novel is a complex form of literature that explores issues in life, including social, moral, religious, and other values. Novelist Dee Lestari, with her work Rapijali: 1 Mencari, introduces teenage characters to depict ideologies in her work. Ideology in the novel serves the purpose of proposing change, improving systems, or altering behavior. This research analyzes the ideology in Dee Lestari's novel using van Dijk's Critical Discourse Analysis. The research method employed is content analysis, collecting data from the novel Rapijali: 1 Mencari and identifying implicit ideologies in themes such as family, politics, music, and friendship. The research findings reveal four ideologies: Humanism, Authoritarianism, Democracy, and Liberalism. This study illustrates how ideologies can be reflected in social, political, and cultural relationships, emphasizing the importance of understanding ideology in literary analysis.